The quality of cost accounting systems in manufacturing firms: A literature review - Qais Yaser Saleh; Munther Barakat AL-Nimer; Sinan S. Abbadi (Cogent Business & Management, 2023)
The objective of this research is to review and synthesize the existing literature on the quality of Cost Accounting Systems (CAS) by manufacturing firms. A Systematic Literature Review (SLR) approach was used by adopting (170) articles in this field published from (2015) to (2023) and obtained from the Scopus database. The research found that traditional CAS is the main determinant of manufacturing firms. Therefore, the current research focuses on the quality of CAS, the benefits of the modern quality of CAS, and the challenges and methods of practicing the quality of CAS in manufacturing firms. This review comes to the idea that implementing CAS will enhance the performance of manufacturing firms and will assist with the preparation of various financial statements and decision-making. The results of the research shed light on the importance of the skills that accountants must possess in the current era and what is the role assigned. Thus, the contribution of this research is to provide integrated knowledge about the effects of recent technology innovations on the accountant's job and skills. Professional firms and regulators consider the findings when reporting on the adaptation of guidelines, policies, and laws for the new environment.
Keywords: 650; Quality; systematic literature review; manufacturing firms; cost accounting systems; cost information